2017
DOI: 10.1111/pce.13065
|View full text |Cite
|
Sign up to set email alerts
|

Are plants sentient?

Abstract: Feelings in humans are mental states representing groups of physiological functions that usually have defined behavioural purposes. Feelings, being evolutionarily ancient, are thought to be coordinated in the brain stem of animals. One function of the brain is to prioritise between competing mental states and, thus, groups of physiological functions and in turn behaviour. Plants use groups of coordinated physiological activities to deal with defined environmental situations but currently have no known mental s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 116 publications
(186 reference statements)
1
40
0
Order By: Relevance
“…When seeds ‘decide’ to germinate, or to activate dormancy processes, can be interpreted as a form of ‘intelligent behaviour’ (Trewavas, 2017). Trewavas asserted that the process of germination and the molecular and hormonal mechanisms involved in seed growth cannot be considered ‘behaviours’ but are essential actions for survival: “Without that, the individual does not develop at all.” Conversely, when the seed ‘decides’ to sprout, it can be considered a manifestation of plasticity, conditioned by the analysis of different environmental variables, and a potential ‘intelligent behaviour’ (Calvo et al, 2017; Trewavas, 2017). This analysis may seem forced, but perhaps the critical points expressed by some (Alpi et al, 2007; Adams, 2018; Taiz et al, 2019) are conditioned by an anthropocentric view of the phenomenon.…”
Section: Seeds: Between Dispersal and Germination Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…When seeds ‘decide’ to germinate, or to activate dormancy processes, can be interpreted as a form of ‘intelligent behaviour’ (Trewavas, 2017). Trewavas asserted that the process of germination and the molecular and hormonal mechanisms involved in seed growth cannot be considered ‘behaviours’ but are essential actions for survival: “Without that, the individual does not develop at all.” Conversely, when the seed ‘decides’ to sprout, it can be considered a manifestation of plasticity, conditioned by the analysis of different environmental variables, and a potential ‘intelligent behaviour’ (Calvo et al, 2017; Trewavas, 2017). This analysis may seem forced, but perhaps the critical points expressed by some (Alpi et al, 2007; Adams, 2018; Taiz et al, 2019) are conditioned by an anthropocentric view of the phenomenon.…”
Section: Seeds: Between Dispersal and Germination Strategiesmentioning
confidence: 99%
“…Nowadays, many biological science theorists are broadening the human concepts of memory, learning and communication beyond the animal kingdom and diverting their attention more towards the plant kingdom to understand these complex mechanisms (van Loon, 2016). Indeed, in the last 20 years, various studies have identified the ability of plants to ‘learn’ and ‘make choices’ (Trewavas, 2003; Ballare & Trewavas, 2009; Trewavas, 2012; Gagliano et al, 2016; Trewavas, 2016; Calvo et al, 2017; Gagliano et al, 2018; Segundo‐Ortin & Calvo, 2019). Some botanists and ecologists have observed how different areas of a plant, from the roots to the flowers, show ‘sentient’ attributes after specific stimulations from the environment (Gagliano et al, 2016; Gagliano et al, 2017; Gruntman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no study showed that plants are sentient. Plants or mushrooms have no organs with which to centralize information and create or process mental states (e.g., feelings) (Calvo et al, 2017; but see Pelizzon and Gagliano, 2015). However, this conceptualization of sentience as something needing centralization of information is quite human-centered.…”
Section: Extending Ethics To Non-animal Beingsmentioning
confidence: 99%
“…However, this conceptualization of sentience as something needing centralization of information is quite human-centered. Even if plants and mushrooms are not capable of sentience, they are at least capable of reception and integration of different information sources [e.g., chemical, visual, and tactile (Trewavas, 2016;Calvo et al, 2017)]. Some recent studies have shown that they are able to learn, react to mechanical stress, and even communicate (Poelman et al, 2012) about this stress (Khait et al, 2019).…”
Section: Extending Ethics To Non-animal Beingsmentioning
confidence: 99%
“…Slowly, the true extent of plant intelligence is being comprehended (Mancuso and Viola 2015;Trewavas 2016;Haskell 2017). Indeed (Calvo et al 2017…”
Section: Howevermentioning
confidence: 99%